Changes of intuition in paranoid personality disorder - Jacobs, Kerrin Artemis (Frontiers in Psychiatry, 2024)
Wherever psychopathology operates with the concept of (disorders of) the self and personality, it can address the role of the intuitive access we have towards ourselves, others, and the world. This paper discusses the concept of oikeiôsis. It examines its role in explaining paranoia as a change in intuitive self-and-world-relatedness. In a first step symptomatic features of paranoid personality disorder are sketched, with a focus on the explanatory role of the attentional and interpretative biases, which correlate with significant changes in intuitive processing. In a second step the prototypical phenomenality of feelings of unfamiliarity and mistrust are discussed against the backdrop of changes of oikeiôsis in paranoid personality disorder. In a third step the main therapeutic challenge in treating paranoid personality disorderbuilding a trustful relationshipis explored. It is concluded that the notion of oikeiôsis resonates particularly with introspection-based therapeutic approaches.Paranoia is a symptom found in several psychopathological conditions. The spectrum of paranoid reactions has been suggested to build a continuum (Elahi et al. 2017 [1] ; Bernstein and Useda 2007 [2] ; Millon et at. 2004 [3] ) reaching from neurotic forms (F23.2) of a paranoid tendency, which are held not to be uncommon also in the general population (Torgensen 2005 [4] ; Freeman 2006 [5] ) to paranoid